THANK YOU FOR CALLING CALIFORNIANS FOR COMMON SENSE YESTERDAY REQUESTING INFORMATION ON THE SMOKING PROHIBITONS INITIATIVE WHICH WILL BE ON THE NOVEMBER GENERAL ELECTION BALLOT IN CALIFORNIA. - TODD AR (Tufts Archival Research Center, 2007)
Missing Attachments; Letter from Californians for Common Sense (CCS) to Gloria Kanner of the Continental Can Company. Thanks Kanner for calling CCS and requesting information on a smoking prohibitions initiative. Discusses components of CCS. Asks for endorsement. Argues proposition neglects individual rights, excessively burdens the business community, and will be expensive and hard to enforce.